Intraoperative Core Temperature Patterns, Transfusion Requirement, and Hospital Duration in Patients Warmed with Forced Air. (February 2015) - Sun, Zhuo; Honar, Hooman; Sessler, Daniel I.; Dalton, Jarrod E.; Yang, Dongsheng; Panjasawatwong, Krit; Deroee, Armin F.; Salmasi, Vafi; Saager, Leif; Kurz, Andrea
Abstract : Background: Core temperature patterns in patients warmed with forced air remain poorly characterized. Also unknown is the extent to which transient and mild intraoperative hypothermia contributes to adverse outcomes in broad populations. Methods: We evaluated esophageal (core) temperatures in 58, 814 adults having surgery lasting >60 min who were warmed with forced air. Independent associations between hypothermic exposure and transfusion requirement and duration of hospitalization were evaluated. Results: In every percentile subgroup, core temperature decreased during the first hour and subsequently increased. The mean lowest core temperature during the first hour was 35.7 ± 0.6°C. Sixty-four percent of the patients reached a core temperature threshold of <36°C 45 min after induction; 29% reached a core temperature threshold of <35.5°C. Nearly half the patients had continuous core temperatures <36°C for more than an hour, and 20% of the patients were <35.5°C for more than an hour. Twenty percent of patients had continuous core temperatures <36°C for more than 2 h, and 8% of the patients were below 35.5°C for more than 2 h. Hypothermia was independently associated with both transfusions and duration of hospitalization, although the prolongation of hospitalization was small. Conclusions: Even in actively warmed patients, hypothermia is routine during the first hour of anesthesia. Thereafter, average core temperatures progressively increase. Nonetheless, intraoperative hypothermia was common, and often prolonged. Hypothermia was associated with increased transfusion requirement, which is consistent with numerous randomized trials. Abstract : In almost 59, 000 adults having surgery lasting more than an hour, core temperatures decreased during the first hour of surgery, thereafter rising to an average final temperature of 36.3°C. Hypothermia significantly increased both transfusion requirements and duration of hospitalization, but only the increase in transfusions was clinically important.